The role of demographics in precipitating crises in financial institutions - Diane J. Macunovich (Institute for the Study of Labor (IZA), 2009)
There are significant effects of changing demographics on economic indicators: growth in GDP especially, but also the current account balance and gross capital formation. The 15-24 age group appears to be one of the key age groups in these effects, with increases in that age group exerting strong positive effects on GDP growth, and negative effects on the CAB and GCF. There have been major shifts in the share of the population aged 15-24 during the past half century or more, many of which correspond closely to periods of institutional turmoil. The hypothesis presented in this paper is that increases in the share of the 15-24 age group lead producers to ratchet up their production expectations and take out loans to expand production capacity; but then reductions in that share - or even declining rates of increase - confound these expectations and precipitate a downward spiral of missed loan payments and even defaults and bankruptcies, putting pressure on central banks and causing foreign investors to withdraw funds and speculators to unload the local currency. This appears to have been the pattern not only during the 1996-98 crisis with the Asian Tigers, but also during the Tequila crisis of the early 1990s, the crises that occurred in the early 1980s among developed as well as developing nations, and the economic problems Japan has experienced since about 1990. The effect appears to be even more pronounced for the current 2008-2009 period.
urn:nbn:de:101:1-200910141155
Keywords: J1; E3; F3; F4; 330; Age structure; currency crisis; demographic change; financial crisis; Altersstruktur der Bevölkerung; Bevölkerungsentwicklung; Bevölkerungsökonomie; Wirtschaftswachstum; Leistungsbilanz; Investition; Sparen; Schulden; Bankenkrise; Finanzmarktkrise; Welt; Schwellenländer